The Anticancer Activity of Srikaya Leaves Fraction (Annona squamosa L.): An In Vitro Study - Makbruri Amin; Irsan Saleh; Rachmat Hidayat (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2019)
Abstract Introduction: Anticancer drugs are aimed primarily at inhibiting the growth and proliferation of cancer cells. Srikaya leaves (Annona squamosa L.) had been proven to possess various therapeutic effects and potential to be developed as anticancer drugs due to its cytotoxic activity. Aim of study: This study aimed to assess the anticancer activity of srikaya leaves (Annona squamosa L.) fraction. Methods: Methanol fraction of srikaya leaves were obtained at concentrations of 500; 250; 125; 62.5; 31.25 µg/ml. Srikaya methanol fraction and cisplatin as control were given to a plate that was sealed with T47D cells for MTT assay. Identification of compounds in the methanol fraction of srikaya leaves was performed with thin layer chromatography (TLC). Data were collected in the form of absorbance value and half-maximal inhibitory concentration (IC50) value was determined ​​by linear regression. Data analysis was carried out with paired T test, unpaired T test, and ANOVA. Results: Average percentage of T47D cells viability increased with the decrease in the concentration of srikaya methanol fraction. Obtained IC50 value was 174.25 µg/ml which was quite active and potential to be developed as an anticancer drug. Methanol fraction of srikaya leaves contained secondary terpenoid metabolites, steroids, phenols, flavonoids, alkaloids and tannins. Flavonoid was the dominant metabolites in phytochemical tests and believed to play a major role in cytotoxic activity of srikaya leaves. Conclusion: Methanol fraction of srikaya leaves possessed the cytotoxic effect on T47D cancer cell line through the role of flavonoid metabolites. Keywords: srikaya, Annona squamosa, anticancer, T47D cells